2017
DOI: 10.1186/s13660-017-1529-2
|View full text |Cite
|
Sign up to set email alerts
|

Robust solutions to box-constrained stochastic linear variational inequality problem

Abstract: We present a new method for solving the box-constrained stochastic linear variational inequality problem with three special types of uncertainty sets. Most previous methods, such as the expected value and expected residual minimization, need the probability distribution information of the stochastic variables. In contrast, we give the robust reformulation and reformulate the problem as a quadratically constrained quadratic program or convex program with a conic quadratic inequality quadratic program, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In 1966, Hartman and Stampacchia [24] first introduced the variational inequality problem (VIP) for used in the study of partial differential equations with unilateral boundary conditions and free boundary value problems of elliptic type from mechanics. The VIP has been intensively and wildly studied and it has been found that it also can be applied to real world problems such as equilibrium problems, optimal control problems, machine learning, signal processing and linear inverse problems (see, for example, [15,16,29,30,34,37,50]).…”
Section: Introductionmentioning
confidence: 99%
“…In 1966, Hartman and Stampacchia [24] first introduced the variational inequality problem (VIP) for used in the study of partial differential equations with unilateral boundary conditions and free boundary value problems of elliptic type from mechanics. The VIP has been intensively and wildly studied and it has been found that it also can be applied to real world problems such as equilibrium problems, optimal control problems, machine learning, signal processing and linear inverse problems (see, for example, [15,16,29,30,34,37,50]).…”
Section: Introductionmentioning
confidence: 99%
“…In 1966, Hartman and Stampacchia [21] first introduced the variational inequality problem (VIP) for used in the study of partial differential equations with unilateral boundary conditions and free boundary value problems of elliptic type from mechanics. The VIP has been intensively and wildly studied and it has been found that it also can be applied to real world problems such as equilibrium problems, optimal control problems, machine learning, signal processing and linear inverse problems (see, for example, [14,15,26,27,31,34,46]).…”
Section: Introductionmentioning
confidence: 99%